Resection rates and safety profile of cold vs. hot snare polypectomy in polyps sized 5–10 mm and 11–20 mm. Issue 4 (April 2019) - Gessl, Irina; Waldmann, Elisabeth; Penz, Daniela; Majcher, Barbara; Dokladanska, Angelika; Hinterberger, Anna; Szymanska, Aleksandra; Trauner, Michael; Ferlitsch, Monika
Abstract: Background and aims: Hot snare (HS) is widely used for the resection of adenomas >5 mm. The cold snare (CS) has a better safety profile and is more cost-effective. The aims of this study were to evaluate effectiveness and safety of CS polypectomy (CSP) compared to HS polypectomy (HSP) for adenomas sized 5–10 mm and 11–20 mm. Methods: 4018 colonoscopies performed within "quality certificate for screening colonoscopy" with one polypectomy of an adenoma sized 5–20 mm each were included. Retrieval rates, complete resection rates and complication rates were assessed and compared between CSP and HSP for adenomas sized 5–10 mm and 11–20 mm. Histologic subgroups were additionally assessed. Results: Complete resection rates (5–10 mm: CSP: 89.4% vs. HSP: 87.9%, p = 0.33; 11–20 mm: CSP: 81.8% vs. 80.9%; p = 1), retrieval rates (5–10 mm: CSP: 99.5% vs. HSP: 99.4%, p = 0.76; 11–20 mm: CSP: 100% vs. HSP: 99%, p = 1) and complication rates (5–10 mm: CSP: 0.2% vs. HSP: 0.2%; p = 1; 11–20 mm: CSP: 0% vs. HSP: 1%, p = 1) were equal between CSP and HSP for adenomas sized 5–10 mm as well as 11–20 mm. For serrated adenomas sized 5–10 mm, HSP was superior to CSP (88.7% vs. 77.2%, p < 0.05) regarding the complete resection rate, but not for advanced adenomas (HSP: 89.1% vs. 87.3%, p = 0.69) or adenomas with high-grade dysplasia (HSP: 76.7% vs. 75%, p = 1). Conclusion: This study further supports the use of CSP for polyps sized 5–10 mm and additionally suggests also using CSP for polyps sized 11–20 mm. These findings, as well as the best method for resection of serrated polyps should be validated in further studies.